(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
The methods of financing international trade operation play an important role in the development of foreign trade. Therefore, our research objective is to answer the following problematic question: what is the role of documentary credit in the financing of foreign trade? To do this, we analyzed data taken from the Foreign Bank of Algeria. The results of our study show the importance of documentary credit in financing international trade operations in a global environment shaped by economic uncertainty, legal disparities, and geopolitical risks, this tool continues to be one of the most trusted and widely used instruments in cross-border business relationships.